INFLUENCE OF AFFILIATIVE LEADERSHIP STYLE ON ORGANIZATIONAL PERFORMANCE OF COMMERCIAL STATE CORPORATIONS IN KENYA - Wachira, John Gatithi; Karanja, Dr. Kabare; Iravo, Prof. Mike (European Journal of Business and Strategic Management, 2018)
Purpose: The purpose of this study was to determine the influence of affiliative leadership style on organizational performance of commercial state corporations in Kenya. Methodology: The study adopted Cross sectional survey research design. The target respondents were 35729 middle level staff in the 20 commercial state corporations in Kenya. Stratified sampling was used to select 384 respondents for the study. This study used primary data which was collected through use of structured questionnaires. Data from the questionnaires were analysed using Statistical Packages for Social Sciences (SPSS) to derive descriptive results. Pilot study was conducted to measure the reliability and validity of the questionnaires. The reliability of the instrument was tested using the Cronbach Alpha method. Results: revealed that there was a positive and significant relationship between affiliative leadership and organizational performance (r=0.316, p=0.000). This was supported by a calculated t-statistic of 11.524 which is larger than the critical t-statistic of 1.96 (Kothari, 2011) and a p value of less than the conventional 0.05. Unique contribution to theory, practice and policy: Based on the finding that affiliative leadership positively affect organizational performance, the study recommends that the management should ensure that there is a strong bond across the teams and provide regular positive feedback which can have a powerful impact on performance Keywords: Affiliative leadership, performance